Inhibition of IRE1 modifies the hypoxic regulation of GADD family gene expressions in U87 glioma cells - O. H. Minchenko; I. V. Kryvdiuk; О. O. Riabovol; D. O. Minchenko; S. V. Danilovskyi; О. O. Ratushna (The Ukrainian Biochemical Journal, 2016)
We have studied hypoxic regulation of the expression of genes encoded GADD (growth arrest and DNA damage) family proteins in U87 glioma cells in relation to inhibition of IRE1 (inositol requiring enzyme-1), which controls cell proliferation and tumor growth as a central mediator of endoplasmic reticulum stress. We have shown that hypoxia up-regulates the expression of GADD34, GADD45A, GADD45B, and GADD153 genes, which are related to cell proliferation and apoptosis, in control (transfected by empty vector) glioma cells in gene specific manner. At the same time, the expression level of EIF2AK1 (eukaryotic translation initiation factor 2-alpha kinase 1) and AIFM1 (apoptosis inducing factor, mitochondria associated 1) genes in these cells is down-regulated upon hypoxic condition. It was also shown that inhibition of ІRE1 signaling enzyme function in U87 glioma cells enhances the effect of hypoxia on these genes expression, except EIF2AK1 and AIFM1 genes. Furthermore, the expression of all studied genes in ІRE1 knockdown cells is significantly decreased upon normoxic condition, except GADD45B gene, which expression level is strongly up-regulated. Therefore, the expression level of genes encoding GADD34, GADD45A, GADD45B, GADD153, EIF2AK1, and AIFM1 is affected by hypoxia and by inhibition of IRE1-mediated endoplasmic reticulum stress signaling in gene specific manner and correlates with suppression of glioma cell proliferation upon inhibition of the IRE1 enzyme function.